Calcium carbonate saturation state: on myths and this or that stories. (13th December 2015) - Waldbusser, George G.; Hales, Burke; Haley, Brian A.
Abstract: In a recent opinion article titled "The Omega Myth", Cyronak et al . provide a series of arguments as to why saturation state should not matter to marine calcifiers. In sections of their article, they highlight several aspects of our published work, and unfortunately appear to misinterpret the foundation for the kinetic–energetic hypothesis we have laid out previously. While we are in full agreement that omega sensitivity is not a substrate limitation issue, we more clearly detail below what a kinetic limitation means and why it is different from a substrate limitation. The kinetic argument we have previously presented highlights how the energetic cost of calcification increases with a decreasing saturation state (or omega). We then highlight several issues with a bicarbonate/proton flux model applied to newly developing marine bivalve larvae, and discuss how a bicarbonate/proton flux and omega-based sensitivity model do not have to be mutually exclusive. Our intent with this comment is to clarify the points raised by Cyronak et al . about our work, and help to move the thinking past dialectic debate towards a more synthetic view on ocean acidification impacts on marine calcifiers.